The Effectiveness of Using Canva as a Medium for Learning Arabic Today - Idham Arkan Ramadhan; Salhab, Reham (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
This study investigates the effectiveness of using Canva as an innovative digital medium for learning Arabic in contemporary educational settings. As technology integration becomes increasingly essential in language classrooms, Canva offers diverse visual and interactive features that support creative and student-centered learning. Employing a mixed-methods design, the research collected data through student questionnaires, classroom observations, and learning outcome assessments involving learners at various proficiency levels. The study aims to determine how Canva influences students’ motivation, vocabulary mastery, comprehension of grammatical structures, and overall engagement in Arabic learning activities. The results reveal that Canva significantly enhances students’ interest by providing visually appealing learning materials, such as infographics, flashcards, posters, and animated presentations. These features help simplify complex linguistic concepts, making them easier to understand and remember. Students also report feeling more motivated and confident because Canva allows them to participate actively in designing their own learning products, thereby fostering autonomy and creativity. Instructors benefit from Canva’s user-friendly interface, which enables them to develop high-quality instructional materials efficiently. Furthermore, the use of Canva promotes collaborative learning, as students often work in groups to produce visual content that supports peer discussion and knowledge sharing. Performance assessments indicate measurable improvements in vocabulary retention and grammar comprehension compared to traditional teaching methods. Overall, the study concludes that Canva is an effective, accessible, and engaging medium that enhances the quality of Arabic language learning today. Its integration into instructional practices offers meaningful opportunities to support modern pedagogical approaches and improve learners’ outcomes.